﻿Molecular docking analysis of ginger (Zingiber officinale) on dopamine compare to bupropion as smoking cessation - Rika Mayasari Alamsyah; Mieke Hemiawati Satari; Sondang Pintauli; Shelly Iskandar (Pensoft Publishers, 2023)
Tobacco use continues to be the leading cause of preventable death worldwide. Smoking is highly addictive because nicotine can stimulate nicotinic acetylcholinergic (nACh) receptors which release dopamine. Smoking cessation can be done with pharmacotherapy such as bupropion or varenicline, but it is associated with side effects. Herbal medicine is a possible easy option for smoking cessation treatment. This study uses ginger as a natural ingredient. Gingerol and shogaol were found to be the active compounds of ginger which are responsible for their pharmacological action and have been identified as TRPV1 agonists. The predictive binding of several forms of gingerol and shogaol to TRPV1 was analyzed using docking analysis in an in silico model. The method used is molecular docking with parameter observations and systematic literature review studies with dopamine as a comparator compound. The results of molecular docking of all herbal compound samples showed that no bioactive compounds had a lower binding energy value than the native ligands. However, all bioactive compounds from ginger show a binding energy value around -8,4 until -7.2 kkal/mol. Based on the molecular docking results, it can be concluded that the ginger herbal compounds have a better interaction potential than the control, although not as good as the native ligands. 12-Shogaol, 8-Shogaol, 12-Gingerol, 10-Shogaol, and 10-Gingerol are thought to target dopamine receptor proteins potentially.